HTLV-1 uveitis - Kamoi, Koju; Mochizuki, Manabu (Frontiers in Microbiology, 2012)
Human T-cell lymphotropic virus type 1 (HTLV-1) is the first retrovirus described as a causative agent of human disease. Following adult T-cell leukemia/lymphoma and HLTV-1-associated myelopathy/tropical spastic paraparesis, HTLV-1 uveitis has been established as a distinct clinical entity caused by HTLV-1 based on seroepidemiological, clinical, and virological studies. HTLV-1 uveitis is one of the most common causes of uveitis in endemic areas of Japan and can be a problematic clinical entity all over the world. HTLV-1 uveitis occurs with a sudden onset of floaters and foggy vision, and is classified as an intermediate uveitis. Analysis of infiltrating cells in eyes with HTLV-1 uveitis revealed that the majority of infiltrating cells were CD3+ T cells, but not malignant cells or leukemic cells based on their T-cell receptor usage. HTLV-1 proviral DNA, HTLV-1 protein, and viral particles were detected from infiltrating cells in eyes with HTLV-1 uveitis. HTLV-1-infected CD4+ T-cell clones established from infiltrating cells in eyes with HTLV-1 uveitis produced large amounts of various inflammatory cytokines, such as IL-1, IL-6, IL-8, TNF-α, and interferon-γ. Taken together, HTLV-1 uveitis is considered to be caused by inflammatory cytokines produced by HTLV-1-infected CD4+ T cells that significantly accumulate in eyes; therefore, topical and/or oral corticosteroid treatment is effective to treat intraocular inflammation in patients with HTLV-1 uveitis. Further investigation is needed to establish a specific treatment for HTLV-1 uveitis.